2022
DOI: 10.3390/ma15072556
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependent on Mechanical and Rheological Properties of EPDM-Based Magnetorheological Elastomers Using Silica Nanoparticles

Abstract: Temperature is one of the most influential factors affecting the performance of elastomer matrix in magnetorheological elastomer (MRE). Previous studies have utilized silica as a reinforcing filler in polymer composite and as a coating material in MRE to improve the thermal stability of the base material. However, the usage of silica as an additive in the thermal stability of MRE has not been explored. Thus, in this study, the effect of silica as an additive on the temperature-dependent mechanical and rheologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
4
8
0
Order By: Relevance
“…The result is in line with a recent study conducted by Rashid et al [21], who found that as the temperature increased from 25 • C to 65 • C, G 0 ′ of MRE has reduced from 0.76 to 0.63 MPa. It is due to the rising temperatures has provided kinetic energy to the molecular chains of polymer, thus allowing the particles to slightly move [21]. Therefore, in accordance with the dropped values of storage modulus of MR foams, it is expected that the rising temperatures also contributed to the increment in the kinetic energy of molecular chains of MR foam, resulting in the particles movement slightly.…”
Section: Strain Sweep Analysis Of Mr Foamsupporting
confidence: 93%
See 3 more Smart Citations
“…The result is in line with a recent study conducted by Rashid et al [21], who found that as the temperature increased from 25 • C to 65 • C, G 0 ′ of MRE has reduced from 0.76 to 0.63 MPa. It is due to the rising temperatures has provided kinetic energy to the molecular chains of polymer, thus allowing the particles to slightly move [21]. Therefore, in accordance with the dropped values of storage modulus of MR foams, it is expected that the rising temperatures also contributed to the increment in the kinetic energy of molecular chains of MR foam, resulting in the particles movement slightly.…”
Section: Strain Sweep Analysis Of Mr Foamsupporting
confidence: 93%
“…Besides, a previous study of basic PU foam has stated that the changed in temperature during service performance have caused changes in the macroscopic properties of the material, such as loss in strength and modulus [30]. The result is in line with a recent study conducted by Rashid et al [21], who found that as the temperature increased from 25 • C to 65 • C, G 0 ′ of MRE has reduced from 0.76 to 0.63 MPa. It is due to the rising temperatures has provided kinetic energy to the molecular chains of polymer, thus allowing the particles to slightly move [21].…”
Section: Strain Sweep Analysis Of Mr Foamsupporting
confidence: 84%
See 2 more Smart Citations
“…Magnetorheological elastomer is known to be highly susceptible to temperature [ 7 , 8 ], humidity [ 9 ], heat [ 10 , 11 ], chemical attack [ 12 ], and moisture [ 13 ], all of which degrade performance [ 14 ]. Furthermore, while MRE properties can be degraded incrementally during fabrication, operation, and storage, environmental exposure can cause the most significant degradation.…”
Section: Introductionmentioning
confidence: 99%